Clinical Applications of 18F-FDG PET/CT in Monitoring Anti-cancer Therapies - Wu, Peilin; Zhang, Yingqiang; Sun, Yi; Shi, Ximin; Li, Fang; Zhu, Zhaohui (Current Pharmaceutical Biotechnology, 2013)
Cancer is becoming the largest threat to human health. Apart from classical anti-cancer therapies such as surgery, chemotherapies, and radiotherapy, many new therapies are being developed or translated into clinical use. These therapies include various neoadjuvant chemotherapies, minimally invasive treatments, and molecular-targeted therapies. However, none of these methods benefit all patients because treatment should be personalized according to the response of each patient. A futile therapy makes a patient miss the optimum time for treatment and increases the medical burden to the society. Thus, a great challenge is encountered in monitoring such therapies. Classical methods based on anatomical changes such as computed tomography (CT) and magnetic resonance imaging (MRI) have well-known limitations in early response evaluation. Positron emission tomography (PET) using 18F-fluorodeoxyglucose (FDG) as tracer is a promising method especially when integrated with CT or MRI in one system. This article reviews the current status of monitoring anti-cancer therapies, including the evolution of evaluation criteria from the World Health Organization to the Response Evaluation Criteria in Solid Tumor and the PET Response Criteria in Solid Tumor. The advantages of 18F-FDG PET/CT for response evaluation are analyzed in various malignant tumors, and the pertinent weaknesses are discussed. Finally, several future directions in monitoring anti-cancer therapies are prospected.
Keywords: PET/CT